2021
DOI: 10.1038/s41467-021-21553-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between antecedent statin use and decreased mortality in hospitalized patients with COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) can result in a hyperinflammatory state, leading to acute respiratory distress syndrome (ARDS), myocardial injury, and thrombotic complications, among other sequelae. Statins, which are known to have anti-inflammatory and antithrombotic properties, have been studied in the setting of other viral infections, but their benefit has not been assessed in COVID-19. This is a retrospective analysis of patients admitted with COVID-19 from February 1st through May 12th, 2020 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
118
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 48 publications
4
118
0
3
Order By: Relevance
“… 75 Another study showed that outpatient statin treatment was associated with decreased COVID-19 mortality, although only 77% of outpatient-treated patients continued statin treatment after hospital admission. 76 If statins are withdrawn at the time of hospital admission, their beneficial effects are likely to be reduced. 77 , 78 Thus, statin treatment should be continued (or started) after hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“… 75 Another study showed that outpatient statin treatment was associated with decreased COVID-19 mortality, although only 77% of outpatient-treated patients continued statin treatment after hospital admission. 76 If statins are withdrawn at the time of hospital admission, their beneficial effects are likely to be reduced. 77 , 78 Thus, statin treatment should be continued (or started) after hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 502 articles were identified by searching the database and related websites. After deduplication, record screening and eligibility assessment, 28 studies remained for qualitative synthesis, as shown in Table 1 [ 11 , 12 , 14 , 20–44 ]. Overall, these 28 selected articles evaluated 86,835 individuals with COVID-19 infection ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The last column of Table 1 detailed the outcomes of each study. Finally, 22 studies were eligible for quantitative synthesis [ 11 , 12 , 14 , 20–23 , 25 , 27 , 29 , 32–34 , 36–44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not have information on whether our treated COVID-19 inpatients had also been treated as outpatients, although it is likely that many who had been treated as outpatients continued their treatment after hospital admission. However, several individual studies [e.g., [68][69][70][71][72] and meta-analyses [73,74] of statin treatment have yielded conflicting results. In these studies, treatment was ascertained largely on the basis of outpatient (not inpatient) information.…”
Section: Discussionmentioning
confidence: 99%